2020
DOI: 10.1186/s12943-020-01262-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of ubiquitination and deubiquitination in cancer metabolism

Abstract: Metabolic reprogramming, including enhanced biosynthesis of macromolecules, altered energy metabolism, and maintenance of redox homeostasis, is considered a hallmark of cancer, sustaining cancer cell growth. Multiple signaling pathways, transcription factors and metabolic enzymes participate in the modulation of cancer metabolism and thus, metabolic reprogramming is a highly complex process. Recent studies have observed that ubiquitination and deubiquitination are involved in the regulation of metabolic reprog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
209
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 277 publications
(210 citation statements)
references
References 306 publications
(354 reference statements)
0
209
0
1
Order By: Relevance
“…Other signaling pathways enriched in our analysis may also play role in cancer polyploidy. Accordingly, the protein ubiquitination pathway which is highlighted in our study has previously shown to be involved in DNA damage repair, tumor proliferation, hypoxia adaptation, and cancer stem cell modulation to chemotherapy resistance [26,[38][39][40][41][42][43]. Also, several recent studies demonstrated the role of FAT10 in chemoresistance [24] and epithelial to mesenchymal transition [25], both of which are associated with cancer polyploidy [44].…”
Section: Discussionmentioning
confidence: 63%
“…Other signaling pathways enriched in our analysis may also play role in cancer polyploidy. Accordingly, the protein ubiquitination pathway which is highlighted in our study has previously shown to be involved in DNA damage repair, tumor proliferation, hypoxia adaptation, and cancer stem cell modulation to chemotherapy resistance [26,[38][39][40][41][42][43]. Also, several recent studies demonstrated the role of FAT10 in chemoresistance [24] and epithelial to mesenchymal transition [25], both of which are associated with cancer polyploidy [44].…”
Section: Discussionmentioning
confidence: 63%
“…Recently, research suggests that ccRCC is a metabolic disease with metabolic reprogramming covering a wide range of biological processes, such as fatty acid metabolism, aerobic glycolysis and amino acid metabolism [49]. As a key pathway for protein degradation, UPS is also reported to be an essential modulator of cancer metabolism [50]. Obviously, there requires more studies and efforts focusing on this field to develop novel diagnostic and therapeutic methods.…”
Section: Discussionmentioning
confidence: 99%
“…From this aspect, controlling cancer energy metabolism becomes a potential treatment. Besides, APC/C CDC20 as an E3 ubiquitin ligase can also promote substrate ubiquitination and their subsequent degradation by the proteasome, which can regulate metabolic signaling pathways, transcription factors, and metabolic enzymes [52]. These show that CDC20 attaches great importance to OC and can be a speci c target to treat OC.…”
Section: Discussionmentioning
confidence: 99%